The Lag Structure of the Impact of Business Ownership on Economic Performance in OECD Countries - Martin Carree; Roy Thurik (Max Planck Institute of Economics, 2006)
This note investigates the impact of changes in the number of business owners on three measures of economic performance, viz. employment growth, GDP growth and labor productivity growth. Particular attention is devoted to the lag structure. The analysis is performed at the country level for 21 OECD countries. Our results confirm earlier evidence on three stages in the impact of entry on economic growth: an initial direct positive effect, followed by a negative effect due to exiting capacities and finally a stage of positive supply-side effects. The net effect is positive for employment and GDP growth. Changes in the number of business owners have no effect on labor productivity.
Older version: http://hdl.handle.net/10419/24900
Keywords: O40; M13; 330; Business ownership; entrepreneurship; economic growth; lag structure